Instrument Design and Measurement of Dielectric Properties Within Radio Frequency Range - . Harmen; Armansyah H. Tambunan; Edy Hartulistiyoso; I Dewa Made Subrata (Jurnal Keteknikan Pertanian, 2001)
Dielectric properties indicated the ability of a system to store, transmit anf reflect electromagnetic wave energy. Recently, the utilization of the properties in agriculture field tends tio increase. For example, dielectric drying of biological material is based on the product's ability to absorb electromagnetic radiation and convert inyo heat. In addition, lower energy application of the property can be utilitized for non-destructive measurement of water content.For a more broed application, measurement of the property anf the influencing factors is indispensable.